2015
DOI: 10.1039/c4ra12205d
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of inclusion complex of perfluorocarbon compound with β-cyclodextrin for ultrasound contrast agent

Abstract: A novel FC-77/β-CD inclusion complex was prepared and used as a ultrasound imaging contract to enhance the ultrasonic echo signal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…3436 The only example that used the BCD/PFC inclusion complex for an US-related application was recently published. 37 In this work, PFC used for US imaging (FC-77) was complexed with BCD at different PFC/BCD ratios. Even though US imaging potential of the complex was shown, the size of the complex was reaching the micron level depending on the PFC/BCD ratio, resulting in one PFC chain having two BCD molecules in a complex.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3436 The only example that used the BCD/PFC inclusion complex for an US-related application was recently published. 37 In this work, PFC used for US imaging (FC-77) was complexed with BCD at different PFC/BCD ratios. Even though US imaging potential of the complex was shown, the size of the complex was reaching the micron level depending on the PFC/BCD ratio, resulting in one PFC chain having two BCD molecules in a complex.…”
Section: Introductionmentioning
confidence: 99%
“…Later, more work was published, for environmental purposes, to show the pollutant removal potential of the inclusion complex because some perfluorinated compounds, especially perfluoroalkyl carboxylic acid and perfluoroalkylsulfonates, are considered as a new class of persistent organic pollutants. In this regard, inclusion complex formation between BCD and different perfluoroalkyl carboxylic acids and their physicochemical characterization have been deeply studied. The only example that used the BCD/PFC inclusion complex for an US-related application was recently published . In this work, PFC used for US imaging (FC-77) was complexed with BCD at different PFC/BCD ratios.…”
Section: Introductionmentioning
confidence: 99%
“…And b-CD can be readily available from the enzymatic degradation of starch, which makes it possess excellent biocompatibility. [29][30][31][32] Because of its hydrophilic exterior and hydrophobic cavity, b-CD can form inclusion complexes with a wide range of organic molecules possessing a suitable shape and size in water spontaneously, [33][34][35][36] which brings the possibility of removing organic molecules from polluted water. Thus, b-CD has become a unique structural unit in the design and preparation of adsorbents employed in water treatment.…”
Section: Introductionmentioning
confidence: 99%
“…These include a study of the effects of SPFO monomer–micelle exchange rates in the presence of CD, binding constant determination using native and substituted CDs, , the selective association of CD to SPFO in the presence of other hydrocarbon surfactants, and a study of hydrophobic effects on complex formation . It was recently demonstrated that complexation of SPFO by CDs is important to the biomedical field since these perfluorocarbon surfactants can be used as oxygen carriers, imaging contrast agents, delivery agents for pulmonary drugs, and genes. The fate, transport pathways, and persistence of such recalcitrant materials are poorly understood, partly due to their unique surface activity, chemical mobility, and stability when compared with their hydrocarbon counterparts. In spite of the numerous solution studies that have reported the structure of the complexes of β-CD and SPFO, similar studies in the solid state were not reported.…”
Section: Introductionmentioning
confidence: 99%